MENINGKATKAN HASIL BELAJAR IPA MATERI SUMBER DAYA ALAM MELALUI MODEL PEMBELAJARAN MAKE A MATCH PADA SISWA KELAS IV SD - Rosy Rahmawati; Nelis Supriati (IKIP Siliwangi, 2019)
The research aims to understand the achievements and increased study results material science natural resources in class IV SDN 269 Griya Bumi Antapani Bandung .The research is design a Quasi Experimental Research with a Control Group Nonequivalent design .The sample was a class IVA SDN 269 Griya Bumi Antapani as a class experiment and IVB SDN 269 Griya Bumi Antapani as a class control .Of the gains proven the impact study results significant natural resources between grade experiment ( use the model make a match ) and class control ( method varied ) talks .Ketuntasan learn to class experiment is nearly 100 % the class control reaches 66,7 %